Oracle: For The Seven Cardinal Directions

(untitled) (University of Guelph College of Arts, 2026)
These cards were created for a workshop at the Sound, Meaning, Education conference 2023. These Oracle cards are based on "The Torres Cycle" by Wilfrido Terrazas and feature original illustration by Esther Gámez Rubio.